Analyzing the Ability of Various Chosen Medicinal Herbs to Cure Wounds in African Catfish (Clarias gariepinus, Burchell 1822) - Adebisi Musefiu Tiamiyu; Follusho B Bolaji-Alabi; Reuben C Okocha; Isaac O Olatoye; Oluwafemi Bolarinwa Adedeji (Department of Aquaculture, 2023)
Phytomedicines are affordable, safe, and offer great potential for treating and controlling wounds. The effects of herbal supplements on Clarias gariepinus wound healing was investigated. Twenty-four fish (146.4±0.74g) randomised into four paired sub-groups: G1 and G2, G3 and G4, G5 and G6, G7, and G8 were fed formulated rations containing no herbal additive (0.0g/kg), 5.0g/kg of Allium sativum, 10.0g/kg of Chromolaena odorata and 10.0g/kg of Talinum triangulare as feed additive respectively at 5% body weight. On the 21st day, a sterile incision measuring 45.0 mm by 1.0 mm was made on the dorsolateral side of each fish. Subgroups G2, G4, G6, and G8 were intraperitoneally inoculated with 0.1 ml of pathogenic Pseudomonas aeruginosa that had been predetermined (1.4 x106 bacteria/ml), while G1, G3, G5, and G7 were not inoculated. Post-incision, macroscopic parameters (measurements), given as percentage healing rates on days 3, 6, 9, 12, and 15, were used to evaluate the wound closure. Data were analyzed using descriptive statistics and ANOVA at α0.05. On day 3, there were significant differences between the control and treatment groups in the healing pattern (P < 0.05). On day 15 post-incision, G7 had the best healing rate in both inoculated (86.7 percent) and uninoculated (100 percent) fish, while G1 had the lowest healing rate (0.0 percent) and maximum healing rate (64.4 percent), respectively. The findings indicated that Talinum triangulare at a concentration of 10.0 g/kg was the optimum feed additive for promoting wound healing in Clarias gariepinus.